2007
DOI: 10.1160/th07-03-0189
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced platelet aggregation and activation under conditions of hypothermia

Abstract: The effects on platelet function of temperatures attained during hypothermia used in cardiac surgery are controversial. Here we have performed studies on platelet aggregation in whole blood and platelet-rich plasma after stimulation with a range of concentrations of ADP, TRAP, U46619 and PAF at both 28 degrees C and 37 degrees C. Spontaneous aggregation was also measured after addition of saline alone. In citrated blood, spontaneous aggregation was markedly enhanced at 28 degrees C compared with 37 degrees C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 24 publications
7
32
0
3
Order By: Relevance
“…OHCA patients often develop postresuscitation stress responses after cardiac arrest, presumably due to the low-flow state during cardiac arrest, followed by a reperfusion injury, which causes the procoagulative systemic inflammatory response syndrome (Adrie et al, 2005;Koch et al, 2013). Furthermore, several studies have shown increased platelet activity in conjunction with mild induced hypothermia (Xavier et al, 2007;Högberg et al, 2009;Scharbert et al, 2010;Ortmann et al, 2012). These factors that strengthen hemostasis in OHCA patients during hypothermia are offset by delayed and slower clot formation demonstrated with thromboelastometry in this and previous studies (Heinius et al, 2002;Shimokawa et al, 2003;Martini et al, 2008;Rundgren and Engström, 2008;Spiel et al, 2009;Ivan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…OHCA patients often develop postresuscitation stress responses after cardiac arrest, presumably due to the low-flow state during cardiac arrest, followed by a reperfusion injury, which causes the procoagulative systemic inflammatory response syndrome (Adrie et al, 2005;Koch et al, 2013). Furthermore, several studies have shown increased platelet activity in conjunction with mild induced hypothermia (Xavier et al, 2007;Högberg et al, 2009;Scharbert et al, 2010;Ortmann et al, 2012). These factors that strengthen hemostasis in OHCA patients during hypothermia are offset by delayed and slower clot formation demonstrated with thromboelastometry in this and previous studies (Heinius et al, 2002;Shimokawa et al, 2003;Martini et al, 2008;Rundgren and Engström, 2008;Spiel et al, 2009;Ivan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Peroxides and thromboxane A 2 cause new platelets to adhere to the old ones, a positive feedback phenomenon termed platelet aggregation, which rapidly creates a platelet plug inside the vessel [36].…”
Section: Positive Feedback Of Platelet Aggregationmentioning
confidence: 99%
“…However, the evidence on how hypothermia per se affects platelet function is contradictory. Whereas some authors proposed an inhibition of platelet function at in vivo and in vitro hypothermia [3,4,[12][13][14][15][16], others suggested platelet activation [17][18][19][20]. Most studies were carried out at temperatures below 28 C and therefore may not reflect platelet function at the clinically relevant degrees of mild and moderate hypothermia.…”
Section: Introductionmentioning
confidence: 99%